Factors affecting mechanical nociceptive thresholds in healthy sows. (May 2016) - Nalon, Elena; Maes, Dominiek; Piepers, Sofie; Taylor, Polly; van Riet, Miriam MJ; Janssens, Geert PJ; Millet, Sam; Tuyttens, Frank AM
Abstract: Objective: To describe anatomical and methodological factors influencing mechanical nociceptive thresholds (MNTs) and intra-site variability in healthy sows. Study design: Prospective, randomized validation. Animals: Eight pregnant, healthy, mixed-parity sows (176–269 kg). Methods: Repeated MNT measurements were taken: 1) with a hand-held probe and a limb-mounted actuator connected to a digital algometer; 2) at nine landmarks on the limbs and tail; and 3) at 1 and 3 minute intervals. Data were analysed using linear mixed regression models. Results: The MNTs (±SEM) of the limbs were lower with the probe (14.7 ± 1.2 N) than with the actuator (21.3 ± 1.2 N; p < 0.001), in the pelvic versus the thoracic limbs (16.7 ± 1.2 versus 19.2 ± 1.2 N; p < 0.001), and in the lateral versus the dorsal metatarsi and metacarpi (17.6 ± 1.2 versus 18.4 ± 1.2 N; p = 0.002). MNTs were higher in all subsequent measurements compared with the first ( p < 0.001) and in the morning compared with the afternoon ( p = 0.04). We found no evidence of MNT differences based on interval between consecutive measurements (1 versus 3 minutes). Variability was lower in the thoracic limbs [mean back-transformed log10 coefficient of variation (CV) ± SE = 25.5 ± 1.5% versus 30.6 ± 1.5% in the pelvic limbs; p < 0.001], with the actuator (22.7 ± 1.5% versus 33.4 ± 1.5% with the probe; p < 0.001), and on the left (CV = 26.9 ± 1.5% versus 29.3 ± 1.5% on the right; p = 0.01). Tail data (probe only) were analysed separately: mean MNT (± SE) was 11.7 (±1.8); MNT increased in days 3–6 of testing compared with day 1 ( p < 0.001). The mean CV (±SE) was 38.9% (±1.1%). Conclusions and clinical relevance: MNTs and intra-site variability in healthy sows were affected by several factors, indicating that this methodology requires considerable attention to detail.